2007
DOI: 10.5194/acp-7-2917-2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of model chemistry and data biases on stratospheric ozone assimilation

Abstract: Abstract. The innovations or observation minus forecast (O–F) residuals produced by a data assimilation system provide a convenient metric of evaluating global analyses. In this study, O–F statistics from the Global Ozone Assimilation Testing System (GOATS) are used to examine how ozone assimilation products and their associated O–F statistics depend on input data biases and ozone photochemistry parameterizations (OPP). All the GOATS results shown are based on a 6-h forecast and analysis cycle using observatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The applied observation errors for MIPAS were of similar size (5%) as the values used for MLS in this study. Coy et al (2007) showed improved analyses in the upper stratosphere when using a linear chemical scheme instead of no chemical scheme when assimilating only SBUV-2 observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applied observation errors for MIPAS were of similar size (5%) as the values used for MLS in this study. Coy et al (2007) showed improved analyses in the upper stratosphere when using a linear chemical scheme instead of no chemical scheme when assimilating only SBUV-2 observations.…”
Section: Discussionmentioning
confidence: 99%
“…(2007) compare different ozone assimilation systems based on linear chemistry schemes. Coy et al (2007) investigate the influence of observation and model biases for the assimilation by a model system with and without a linear chemical scheme. As pointed out in a review by Lahoz et al (2007), using data assimilation systems based on CTMs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It uses lookup tables of diurnally averaged photochemical coefficients derived from a full chemistry model based on linearizing scaled odd-oxygen production and loss rates about equilibrium states. These equilibrium states are specified in the model using zonalmean observational climatologies that are chosen carefully here to match characteristics of the assimilated ozone observations so as to avoid model-data bias (Geer et al, 2007;Coy et al, 2007). The scheme does not at present parameterize either diurnal ozone photochemistry at altitudes above $0:3 hPa or tropospheric ozone chemistry, relaxing ozone in both altitude regions to a reference state based on a mean photochemical relaxation rate.…”
Section: Trace Constituentsmentioning
confidence: 99%
“…However, these results also show that observational gaps can seriously degrade the ozone analyses. Arguably, in the upper stratosphere (fast chemical time-scales), a better solution than omitting chemistry would be to bias correct the Cariolle scheme (see, e.g., Coy et al, 2007).…”
Section: Assimilation Of Ozonementioning
confidence: 99%